Measurement Model of Prahalad’s framework for palm oil in Malaysia - Shaban, Omar Kassim A.; Liu, Yao; Mohd Ridzuan, Nordin (2018)
This study examines how prahalad's market framework impacted brand loyal in the base of the palm Oil market in Malaysia. Although there is a positive correlation between brand loyalty and brand awareness, there is no studies have quantitatively examined all of prahalad's 4As